Mobile Learning: Learning Tools in the Era of Industrial Revolution 4.0 - Jakaria Sembiring; Ambiyar Ambiyar; Unung Verawardina; Firman Edi; Oskah Dakhi (Universitas Muhammadiyah Enrekang, 2022)
The application and adaptation of technology in the learning space is very important to keep up with the changing times of globalization. The development of information and communication technology has had an impact on the world of education, especially the learning process. The purpose of this research is to find literature on mobile learning and its applications as well as the tools used in the learning process for educators and learners in the 21st century. The research findings from the literature show that the use of mobile technology affects the development of mobile learning applications as a tool in the learning process in the 21st century. Mobile learning applications can be used by educators and learners as long as they are connected to the internet. The development of mobile applications makes educators must master its use. Learners can also use the application to store their knowledge about the required teaching materials. The conclusion from this research is that